Neonatal hypokalemia - Sarici D; Sarici SU (Dove Medical Press, 2012)
Dilek Sarici1, S Umit Sarici21Kecioren Research and Education Hospital, Kecioren, Ankara, 2Chief of Division of Neonatology, Division of Neonatology, Department of Pediatrics, Gulhane Military Medical Academy, Ankara, TurkeyAbstract: In this article, distribution of potassium (K+) in body fluids, pathophysiology, causes, clinical signs and symptoms, and the evaluation and treatment of neonatal hypokalemia are reviewed. K+ is the most important intracellular cation and normal serum K+ is stabilized between 3.5 and 5.5 mEq/L. Hypokalemia may be caused by increased renal losses, increased extrarenal (gastrointestinal) losses, redistribution or prolonged insufficient K+ intake. Clinical signs and symptoms occur as the result of functional changes in striated muscle, smooth muscle, and the heart. Hypokalemia is usually asymptomatic when K+ levels are between 3.0 and 3.5 mEq/L; however, there may sometimes be slight muscle weakness. Moderate hypokalemia is observed when serum K+ is between 2.5 and 3.0 mEq/L. Proximal muscle weakness is observed most commonly in lower extremities; cranial muscles are normal, but constipation and distention are prominent. Severe hypokalemia develops when serum K+ falls below 2.5 mEq/L. Rhabdomyolysis, myoglobinuria, severe muscle weakness, paralysis, respiratory distress, and respiratory arrest are observed. The clinical signs and symptoms may be unremarkable in cases of chronically developing hypokalemia; however, appropriate treatment is essential when serum K+ level falls below 2.5 mEq/L as the most dangerous complication of hypokalemia is fatal cardiac arrythmia, and changes visible with electrocardiography may not always correlate with the level of hypokalemia. Sodium (Na+), K+, chloride (Cl-), bicarbonate, creatinine, blood sugar, magnesium (Mg), plasma renin activity, aldosterone, and blood gases should be investigated by laboratory testing. Aspartate aminotransferase, alanine aminotransferase, creatinine kinase, and creatinine kinase isoenzyme MB should be studied if rhabdomyolysis is suspected. In urine sample density, pH, Na+, K+, Cl-, Mg, creatinine, and myoglobinuria (blood reaction is positive in the absence of erythrocytes on microscopic examination of urine) should be investigated. The primary aim of therapy is to prevent and treat life-threatening cardiac and muscular complications. However, in the presence of severe symptomatic hypokalemia and gastrointestinal problems such as ileus, the intravenous route may be used in cases where serum K+ level is usually below 2.6 mEq/L. K+ given in intravenous fluids should not exceed 40 mEq/L. In case of emergency, 0.3–1 mEq/kg of K+ may be given intravenously over 1 hour. When higher concentrations (60–80 mEq/L) are needed, infusion through a central vein under electrocardiography monitoring may be used.Keywords: neonatal, hypokalemia, newborn